Edukasi Kesehatan Dukungan dan Peran Suami pada Ibu Hamil Hipertensi Gestasional Mencegah Terjadinya Preeklampsia di Desa Bangun Rejo Tahun 2024 - Damayanty S; Ade Rachmat Yudiyanto; Marta Armita Br Silaban; Rahmi Larasati; Rauni Gultom (Compromise Journal Community Proffesional Service Journal, 2024)
Hypertension is a disease that can harm pregnant women. Hypertension associated with pregnancy is referred to as gestational hypertension. Pregnancy-related hypertension is defined as hypertension that develops after 20 weeks of pregnancy in a mother who is known to have normal blood pressure, or has normal blood pressure, and does not exhibit severe proteinuria or other symptoms of preeclampsia. If the mother's blood pressure rises above 140/90 mmHg at least twice a week after resting, then it is certain that she is suffering from hypertension. 18 When blood pressure increases to 140/90 mmHg during pregnancy, or when systolic and diastolic pressure increase by 30 and 15 mmHg, respectively, above the normal limit, this is called hypertension. Preeclampsia/eclampsia, gestational hypertension, chronic hypertension with preeclampsia, and chronic hypertension are the four forms of hypertension known to occur during pregnancy. Husband's support has a significant impact on fulfilling her physical and emotional needs. This is especially true for first-time mothers because their experience and understanding of pregnancy is different from adult pregnant women. When compared with adult pregnancies, teenage mothers tend to be more aggressive, depressed and anxious. In addition to psychological and emotional states that are influenced by physical changes, mothers who experience a lack of family attention also experience fear, anxiety and anxiety related to childbirth.